Manajemen Stres Orangtua Dalam Pendampingan Pembelajaran Daring - Heni Listyanti; Ristia Wahyuningsih (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Online learning still has a lot of obstacles that make parents stressed in accompanying their children. Stress coupled without managing can be harmful to you or to others. The aim of this study is to learn how parents manage stress caused by online learning assistance. This study used a qualitative approach. The methods to collect data were observation and interview. The research sample was three mothers in 32-34 years old and their last aducation was Senior High School and D1. The results indicate that parents stressed in online learning assistance caused by the factor of children, teacher and themselves (parents). The ways to manage stress are rest, telling the problem to closest person or others, dividing time of assistance between father and mother.